USM STUDENT BAGS OLYMPICS - COCA COLA AWARD - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
KUBANG KERIAN, November 2015 Universiti Sains Malaysia (USM) student, Fatin Nurfatehah Mat Salleh, who won three gold medals in archery in the 2015 SEA Games, did the university proud when she bagged the 2015 Olympics Award sponsored by CocaCola in Kuala Lumpur recently.